The Influence of Training Load on Hematological Athlete Biological Passport Variables in Elite Cyclists - Astolfi, Tiffany; Crettaz von Roten, Fabienne; Kayser, Bengt; Saugy, Martial; Faiss, Raphael (Frontiers in Sports and Active Living, 2021)
The hematological module of the Athlete Biological Passport (ABP) is used in elite sport for antidoping purposes. Its aim is to better target athletes for testing and to indirectly detect blood doping. The ABP allows to monitor hematological variations in athletes using selected primary blood biomarkers (hemoglobin concentration ([Hb]) and reticulocyte percentage (Ret%)) with an adaptive Bayesian model to set individual upper and lower limits. If values fall without the individual limits, an athlete may be further targeted and ultimately sanctioned. Since [Hb] and Ret% vary with plasma volume (PV) fluctuations, possibly caused by training load changes, we investigated the putative influence of acute and chronic training load changes on the ABP variables. Monthly blood samples were collected over one year in 10 male elite cyclists (25.6 ± 3.4 yrs, 181 ± 4 cm, 71.3 ± 4.9 kg, 6.7 ± 0.8 W.kg-1 5-min maximal power output) to calculate individual ABP profiles and monitor hematological variables. Total hemoglobin mass (Hbmass) and PV were additionally measured by carbon monoxide rebreathing. Acute and chronic training loads – respectively 5 and 42 days before sampling – were calculated considering duration and intensity (training stress score, TSSTM). [Hb] averaged 14.2 ± 0.0 (mean ± SD) g.dL-1 (range: 13.3 to 15.5 g·dl-1) over the study with significant changes over time (P = 0.004). Hbmass was 1030 ± 87 g (range: 842 to 1116 g) with no significant variations over time (P = 0.118), whereas PV was 4309 ± 350 mL (range: 3688 to 4751 mL) with a time-effect observed over the study time (P = 0.014). Higher acute – but not chronic – training loads were associated with significantly decreased [Hb] (P <0.001). Although individual hematological variations were observed, all ABP variables remained within the individually calculated limits. Our results support that acute training load variations significantly affect [Hb], likely due to short-term PV fluctuations, underlining the importance of considering training load when interpreting individual ABP variations for anti-doping purposes.